Working from Home: Does Impact to Work Stress and Performance? Readiness to Change as Moderating Variable - Arifiani, Ratya Shafira; Rumijati, Aniek (JDM (Jurnal Dinamika Manajemen), 2022)
This study examines how the impact of work from home on performance, due to the existence of a new working atmosphere so as to examine whether it has an impact and has an effect on perfor- mance; work from home against work stress. This is due to changes in routine and prone to conflict and role ambiguity that can lead to work stress; readiness for change or readiness to change as mod- eration. Changes in work routines make workers have to adapt to technology and become com- pletely online. This type of research is explanatory research which aims to test the hypothesis. The research method uses a quantitative approach, by distributing questionnaires as primary data and the respondents of this research are teachers in the city of Malang. The analysis tool uses path analysis with SmartPLS 3.0 software. The results showed that work from home had no significant effect on performance; work from home has a significant effect on work stress; work stress has a significant ef- fect on performance; work stress mediates the effect of work from home on performance; readiness to change does not moderate the effect of work from home on performance.